2011
DOI: 10.7863/jum.2011.30.8.1059
|View full text |Cite
|
Sign up to set email alerts
|

Usefulness of the Twinkling Artifact in Identifying Implanted Mesh After Inguinal Hernia Repair

Abstract: Standard gray scale imaging alone is not reliable when identifying inguinal mesh. The twinkling artifact was present in 79% of inguinal regions with mesh when evaluated with a low-frequency curvilinear array transducer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 23 publications
(23 reference statements)
0
16
0
Order By: Relevance
“…Although the 2D hand-held ultrasound (HHUS) has been shown to identify radiolucent foreign bodies [12,16], in our experience, it has not been always reliable in identifying the LW mesh. In ventral hernia repair surgery, mesh may be placed in a variety of locations in relation to the structures of the anterior abdominal wall (Fig.…”
Section: Introductionmentioning
confidence: 74%
See 2 more Smart Citations
“…Although the 2D hand-held ultrasound (HHUS) has been shown to identify radiolucent foreign bodies [12,16], in our experience, it has not been always reliable in identifying the LW mesh. In ventral hernia repair surgery, mesh may be placed in a variety of locations in relation to the structures of the anterior abdominal wall (Fig.…”
Section: Introductionmentioning
confidence: 74%
“…Several reports have shown that compared with simple sutures, mesh is superior, with significantly reduced recurrence rates [8][9][10][11]. However, implanted mesh is a foreign body and is subject to a variety of complications, with recurrence remaining an unsolved problem and reoperation increasingly common [6,12]. Therefore, sonologists now need perform an increasing number of examinations in patients with previously implanted meshes for either repair-related problems or other indications [1].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The idea behind this concept is to be able to diagnose clinical complications frequently observed after mesh implantation, such as shrinkage, tissue erosion, mesh migration and deformation, and for the surgeons to follow the fate of the allogenic material using non‐invasive imaging techniques and consequently to be able to reposition the material if required. It is extremely challenging, or even impossible, with the current clinical imaging devices, such as X‐ray or computerized tomography (CT scan), ultra‐sound and magnetic resonance imaging (MRI), to directly localize the implanted material after its infiltration by the host tissue . Among the different established techniques used clinically to diagnose pathologies and diseases occurring in the human body, MRI is one of the most powerful and widespread techniques.…”
Section: Post‐implantation Visible Meshmentioning
confidence: 99%
“…As a substitute to MRI‐based imaging, ultra‐sound technique has been described as a powerful method for identifying meshes in gynaecology (through a transvaginal approach after pelvic organ prolapse surgeries) . Unfortunately, the intensity and the quality of the signal attenuation is very dependent on the composition of the meshes and on the anatomical region, which limit, for example, the ability to systematically visualize hernia meshes after implantation in some abdominal areas …”
Section: Post‐implantation Visible Meshmentioning
confidence: 99%